Impacts of hexafluoropropylene oxide tetrameric acid (HFPO-TeA) on neurodevelopment and GABAergic signaling in zebrafish larvae - Linlin Wu; Jian Wang; Heyong Ye; Yiyang Yao; Miaoyang Hu; Jie Cheng; Lingcan Kong; Wenwei Liu; Feng Ge (Ecotoxicology and Environmental Safety)
Hexafluoropropylene oxide oligomer acids (HFPOs), an emerging environmental pollutant, are increasingly utilized in the manufacture of fluorinated synthetic materials as a substitute for traditional perfluorooctanoic acid (PFOA), resulting in a corresponding rise in detection rates in aquatic environments, which may present inherent safety hazards to ecosystems and public health. However, few data are available on the issue of their toxicity and mechanism. This study aimed to investigate the potential toxic effects of hexafluoroepoxypropane tetrameric acid (HFPO-TeA), a typical HFPO, on the early developmental stages of zebrafish larvae. It revealed that HFPO-TeA exposure resulted in significant detrimental effects, including adverse impacts on general morphological characteristics, such as eye area, heart rate, and swimming bladder, in zebrafish embryos and larvae. Targeted metabolomics and transcriptomics inquiries clarified that HFPO-TeA exposure reduced the levels of the neurotransmitter gamma-aminobutyric acid (GABA) and downregulated the expression of genes related to the GABA pathway. Simultaneously, transgenic zebrafish exhibited that exposure to HFPO-TeA impedes the growth of GABAergic neurons. Moreover, the molecular docking analysis indicated that GABAA receptors might be the potential targets of HFPO-TeA. Taken together, the current data highlights that the HFPO-TeA might not be safe alternatives to PFOA. This study presented a model for HFPO-TeA-induced neurotoxicity in developing zebrafish that can aid in ecological risk assessments.